Epiphytic bryophytes in urban forests of Wrocław (SW Poland) - Fudali, Ewa; Żołnierz, Ludwik (Biodiversity: Research and Conservation, 2019)
Data documenting the occurrence of epiphytic bryophytes in the urban forests of the Wroclaw city were collected and reported for the first time. Research was carried out in 2015-2016, in forest areas situated within the city administrative boundaries, to find whether some epiphytic species reported from the Wroclaw environs in the 19th century and presently considered to be primeval forest relicts occur in urban forests. The survey was carried out using the established network of 50 study plots randomly scattered within the urban forested areas. In total 42 species (4 liverworts and 38 mosses) were recorded on 467 trees; three of them are primeval forest relicts. In this paper, the host-tree preferences, distribution in the individual forests, relative frequency, abundance and exposure to compass directions of the studied taxa are analysed. Of the species described, only 17 are obligatory epiphytes, while 22 of them are character forest species. However, 82% of the latter were noted on a small number of tree trunks. Two moss taxa, Hypnum cupressiforme and Platygyrium repens, were most frequently found (on 76 and 50% of the trees, respectively). Among the species recorded in the studied area, there are five that have been showing some expansive tendencies in Europe in recent decades. The potential ability of these species to spread in urban areas is discussed in relation to their general ecological requirements.